The Influence of Viewing Time and Color on Architectural Aesthetic Judgment - Dai, Anbang; Wang, Junru; Yu, Jie; Fukuda, Hiroatsu (Frontiers in Psychology, 2022)
Understanding the factors influencing the aesthetic experience of architectures is an important topic in empirical aesthetics. In this study, we examined the effect of 3 architectural factors, i.e., ceiling height, openness, and contour, on viewers’ aesthetic appreciation through a series of experiments. In previous studies on architectural aesthetics, participants were usually asked to view an image of an architectural space for a few seconds. The long viewing time allows them to focus on different parts of the architecture and then make an aesthetic judgment. The long viewing time, however, also makes it difficult to obtain viewers’ aesthetic scores for a large number of architectural spaces in a short period. In this study, we shortened the visual presentation time to 200 ms, which allowed the viewers to have only one fixation on the image, and asked the viewers to make an aesthetic judgment. It was found that the experiment with a 200-ms viewing time could establish how the 3 architectural factors influenced aesthetic judgment as well as previous experiments with a 3000-ms viewing time, suggesting that aesthetic judgment could be made within one fixation. Additionally, we investigated the impact of color on architectural aesthetic judgment by presenting grayscale images. We found that the 3 architectural factors influenced aesthetic judgment in similar ways for both color and grayscale images. In summary, we found that image presentation duration and color were not main factors modulating viewers’ architectural aesthetic judgments, and we also presented a way to quickly obtain aesthetic scores for architectural spaces.